New Machine, Old Cough: Technology and Tuberculosis in Patna - Saria, Vaibhav (Frontiers in Sociology, 2020)
In 2013, a new technology, GeneXpert, was introduced in India, which in addition to testing for TB could also diagnose whether the detected strain was drug resistant. By detecting the bacterium more effectively than other available tests and simultaneously testing for resistance, GeneXpert promised to reduce the delay in diagnosis and hence the ineffective treatments. The new test was introduced to multiple cities via a coalition that included global health funding bodies, the government of India, the World Health Organization, and non-governmental organizations. Despite the concerted effort of the coalition, among formal providers (those trained in biomedicine) in the private sector, the new technology was not adopted as quickly as had been hoped. Examining formal providers’ initial responses to the technology’s introduction in the city of Patna reveals how the adoption of new technology can be influenced by the particularities of local medical market such as the availability of diagnostic tests, presence of informal providers, and reputation of formal providers. While protocols and operations might seem standardized across implementation plans, the work that is required to ensure success must take into account the particular role that the market plays from site to site.